Objective acoustical analysis of room acoustic measurements in Portuguese Roman Catholic churches - A. Carvalho (1994)
This study reports on acoustical field measurements in a major survey of RomanCatholic churches in Portugal that were built in the last 14 centuries. Series of monauralacoustical measurements were taken at several source and receiver locations in eachchurch. The measurements included Reverberation Time, Early Decay Time, Early to LateSound Index, Early to Total Energy Ration, Center Time and Loudness. This paperconcentrates on the relationships among these six room acoustic measures using linear andnon-linear models.